Analysis of Syntax Errors in Writing and Learning Model of Insya’ by Students of the Khadimul Ummah Islamic Boarding School Bintan/ Analisis Kesalahan Sintaks pada Penulisan dan Model Pembelajaran Insya' oleh Santri Pondok Pesantren Khadimul Ummah Bintan - Aidillah Suja; Cahya Edi Setyawan; Tri Murdiono (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2022)
The goal of this study is to determine the types of writing errors that students at the Khadimul Ummah Bintan Islamic Boarding School make in terms of syntactic elements, as well as give methods to reduce the incidence of these errors. Data was collected through interviews, observation, and documentation. The data analysis method employed a 'discourse analysis', which is a type of analysis that looks for patterns in the texts. The micro linguistic units associated to syntax are examined using the discourse analysis in the texts. This method was used to look at data on the suitability of using Arabic in the subject of insya' to detect faults and discrepancies when using Arabic terms. Results of the study show: (1) students of the Khadimul Ummah Bintan Islamic Boarding School have ten different types of writing errors: nakirah and ma'rifah, mudzakkar and muannats, meaningful harf, dhamir usage, mufrad, mutsanna, and jama', i'rab, fi'il, na'at, and man'ut, mu'rabah, and word writing. (2) Methods for reducing these errors include applying the acquisition of Arabic language rules (Nahwu) via deductive or inductive methods, and implementing the integration of learning. The Khadimul Ummah Islamic Boarding School of Bintan is pioneering the insya' learning approach by using the Insya' Muwajjah learning paradigm, which involves giving students several examples of how to correctly organize Arabic words/sentences and a large amount of daily vocabulary while simultaneously writing it down. Abstrak Penelitian ini bertujuan untuk mengetahui bentuk kesalahan tulisan insya’ santri Pondok Pesantren Khadimul Ummah Bintan ditinjau dari aspek sintaksis dan untuk meminimalisir kesalahan menulis. Metode pengumpulan data adalah wawancara, observasi, dan dokumentasi. Metode analisis data menggunakan analisis wacana, yang bertujuan mengetahui pola-pola bahasa yang diekspresikan via teks. Analisis wacana digunakan untuk mengkaji unit bahasa secara mikro, terkait sintaksis yang fokus pada kesesuaian penulisan dan penggunaan Bahasa Arab dalam mata pelajaran insya’. Hasil penelitian ini adalah: (1) ada 10 bentuk kesalahan tulisan insya’ pada santri Pondok Pesantren Khadimul Ummah Bintan pada aspek-aspek berikut ini: nakirah dan ma’rifah, mudzakar dan muannats, harf bermakna, penggunaan dhamir, mufrad. mutsanna, dan jama’, i’rab, fi’il, na’at dan man’ut, mu’rabah, dan penulisan kata. (2) Solusi untuk meminimalisir kesalahan-kesalahan tersebut yaitu: penerapan pembelajaran kaidah Bahasa Arab (Nahwu) dengan metode deduktif atau induktif, menerapkan integrasi pembelajaran kaidah Bahasa Arab (Nahwu) ke dalam pembelajaran insya’ atau sebaliknya, dan melakukan inovasi model pembelajaran insya’ di dalam pondok. Salah satu penerapan model pembelajaran adalah Insya’ Muwajjah dangan memberikan banyak contoh tentang susunan kata/kalimat Bahasa Arab yang benar kepada santri dan memperbanyak kosa-kata harian sekaligus menuliskan kosa kata tersebut.